Comparison of perioperative analgesia between intravenous paracetamol and fentanyl for rigid hysteroscopy. A randomised control trial - Dileep Kumar; Kamal Kumar; Mohammad Hamid (Journal of the Pakistan Medical Association, 2021)
Objective: To compare efficacy of intravenous paracetamol and fentanyl for intra-operative and post-operative analgesia in patients undergoing for diagnostic and therapeutic rigid hysteroscopy. Methods: Prospective Randomized Clinical Trial was conducted at Aga Khan University Hospital, Karachi, from October 2016 to June 2017. Study instituted after ethical review committee approval and patient has ASA-I, II, aged 18-65 years, consented for hysteroscopy. Anesthesia induction technique was standardized and analgesia in group-P, paracetamol 15 mg/Kg administered 15-30 minutes before surgery and in group-F, fentanyl 2 mcg/kg administered at induction of anesthesia. Intraoperative pain was assessed by changes in heart rate, systolic, diastolic and mean arterial blood pressure and postoperative pain was assessed by visual analogue scale. SPSS 19 was used for data analysis. Results: Sixty patients scheduled for hysteroscopy were allocated into two groups. Patient’s ASA status and demographics were found relatively similar in both groups except for age differences (p< 0.011). In paracetamol group, mean SBP at 10,15, 20, 25 and 30 minutes and mean DBP at 20, 25 minutes & Mean arterial blood pressure at 20 minutes were statistically significant (p<0.05) compared to the fentanyl group. However, the mean heart rate was statistically insignificant among the groups. The postoperative visual analogue pain scores were almost similar at 0, 15, and 30 minutes (p>0.05) among the groups. Although, the rescue analgesia was needed in 3 patients on arrival in recovery room in each group. Conclusion: Intravenous paracetamol offers similar analgesic efficacy to fentanyl for rigid hysteroscopy in ambulatory surgery. However, Continuous...